Gain spectrum adjustable laser medium based on structure compounding and preparation method thereof
By structurally combining different types of laser media, combining matrix materials and activated ions, the problems of single attributes and energy transfer of existing laser media materials are solved, and flexible control of the gain spectrum and efficient emission are achieved to meet the needs of special lasers.
Patent Information
- Application Number
- CN202411622744.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing laser dielectric material has a single attribute, and when multiple rare earths are co-doped, it is easy to generate unnecessary energy transfer, resulting in a decrease in emission efficiency and the advantageous characteristics of laser glass and laser crystals cannot be obtained at the same time.
The structural composite method is adopted to combine different types of laser media in series or parallel, combining matrix materials and activation ions to achieve the regulation of the gain spectrum, and avoid unnecessary energy transfer between multiple activation ions.
It realizes flexible matching of the gain medium matrix material and activated ions, improves emission efficiency, and can obtain the characteristics of multiple gain mediums and gain spectrums of different bands at the same time, meeting the application needs of special solid-state lasers.
Smart Images

Figure CN119154073A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of laser technology, and in particular relates to a gain spectrum tunable laser medium based on structural compounding and a preparation method thereof. Background Art
[0002] Laser gain medium is one of the necessary conditions for generating lasers. From the material perspective, the gain medium determines the performance of the final laser, such as key parameters such as gain bandwidth, luminescence peak position and gain coefficient. At present, the control method of laser medium materials is limited to the control of material components, such as network modification ion doping in glass, medium valence ion substitution in crystals, or co-doping of multiple activation ions. The first two methods both achieve broadband or luminescence peak control by changing the local environment around the activation ions, thereby affecting the Stark level splitting of the activation ions; the co-doping of activation ions regulates the spectral characteristics through the energy transfer interaction between the activation ions.
[0003] However, when the spectrum is controlled by changing the local environment around the activated ions, the control limit is often small due to the intrinsic properties of the material or the molding method. For example, laser glass is limited by the glass formation zone, and it is impossible to obtain the advantages of multiple glass types in one glass medium at the same time. Obviously, it is usually impossible to obtain the advantages of laser glass and laser crystal in one medium at the same time. For example, the literature (Er-doped silicate fiber amplifiers in the L-band with flat gain, Vol. 49, No. 4 / 15 February 2024 / Optics Letters) regulates the luminescence properties by doping glass network modifiers such as alkali metals and alkaline earth metals. However, excessive doping of modifiers will lead to a decrease in the thermal properties of the glass.
[0004] When the emission spectrum of laser medium is regulated by co-doping with multiple activated ions, due to the complex energy level structure of activated ions, there is often unavoidable unnecessary energy transfer between multiple ions, resulting in a decrease in the emission efficiency of laser medium materials. 3+ / Er 3+ / Tm 3+ tri-doped tellurite glass with enhanced broadband mid-infrared emission, Optics & Laser Technology 149 (2022) 107904) achieves broadband luminescence by co-doping with multiple rare earth ions. 3+ and Tm 3+ The co-doping of Er 3+The reduction of ion fluorescence lifetime eventually leads to a decrease in luminescence efficiency.
[0005] Therefore, a new type of laser medium is needed, which can combine the basic properties of multiple gain materials, avoid unnecessary energy transfer when multiple activation ions are co-doped, and regulate the gain spectrum; thereby meeting the application requirements of special solid-state lasers. Summary of the invention
[0006] In order to enrich the current laser medium gain spectrum control method and solve the problem that the current laser medium material has a single property and is prone to unnecessary energy transfer when multiple rare earths are co-doped, the present invention provides a gain spectrum tunable laser medium based on structural composite and a preparation method thereof.
[0007] The purpose of the present invention is achieved by at least one of the following technical solutions.
[0008] A gain spectrum tunable laser medium based on structural compounding includes a plurality of different types of laser media of structural compounding; the structural compounding methods include series compounding and parallel compounding; the laser medium includes a matrix material and doped activation ions; the matrix material is laser glass, laser crystal or laser ceramic; the doped activation ions in the laser medium include rare earth ions, transition metal ions or heavy metal ions.
[0009] Further, when the matrix materials of the plurality of different types of laser media are the same, the activation ions doped therein are different; When the active ions doped in the plurality of different types of laser media are the same, their matrix materials are different; Or the active ions doped in the plurality of different types of laser media are all different from the matrix materials; The activated ions doped in the laser medium include rare earth ions (preferably Nd, Yb, Er, Tm, Ho, etc.), transition metal ions (preferably Cr, Mn, etc.) or heavy metal ions (preferably Bi, Te, etc.).
[0010] Furthermore, among the multiple different types of laser media compounded in series, the multiple different types of laser media are pumped sequentially from one end to the other end in the order of the series connection, and the laser passes through the different types of laser media sequentially in the order when transmitting therein.
[0011] Furthermore, in the multiple different types of laser media compounded in parallel, the multiple different types of laser media are pumped simultaneously and generate multiple lights with different characteristics simultaneously, and the multiple lights are transmitted in the laser medium simultaneously.
[0012] Furthermore, among the various types of laser media compounded in a series structure, the hot-melt composite interface between adjacent laser media has an inclination angle of 0 to 10°.
[0013] Furthermore, the length of the laser medium is ≥3 μm in series recombination, and the cross-sectional diameter of the laser medium is ≥3 μm in parallel recombination.
[0014] Furthermore, in the composite interface of any two different laser media, the ion diffusion distance is ≤1.5 μm.
[0015] A method for preparing a gain spectrum tunable laser medium based on structural compounding comprises the following steps: S1. Prepare various types of laser media: S2. Hot-melt partitioned compounding of structural composite laser media: the surfaces of the various types of laser media prepared in step S1 are closely attached according to the set structural compounding method, thereby achieving hot-melt partitioned compounding to obtain a laser medium with adjustable gain spectrum after hot-melt compounding; S3. Cold processing of the laser medium after hot-melt partition composite: At this time, due to the high-temperature hot-melt process, the structurally composited laser medium may have certain micro-deformation or surface damage. According to the direction of the hot-melt bonding interface, the gain spectrum tunable laser medium after hot-melt partition composite is cold processed, including cutting, polishing, etc., to finally obtain a structurally composite gain spectrum tunable laser medium.
[0016] Furthermore, in step S1, for the laser glass gain medium, the laser glass material is prepared by a high temperature melting-annealing method, a sol-gel method, or a 3D printing method, and the molten glass liquid can be cast in a customized mold to obtain a gain medium of a specific shape or a gain medium of a desired shape can be obtained by mechanical processing methods such as cutting and turning. For the laser crystal material, the crystal orientation is selected as required, and mechanical cutting is performed along the crystal plane to obtain a crystal gain medium of a specific shape. After obtaining the laser medium, its surface is optically polished, and the surface roughness Ra is less than 1 μm.
[0017] Furthermore, in step S2, when the laser glasses are heat-melted and composited, the composite interface can be directly bonded; when the laser crystals are heat-melted and composited, or when the laser crystal and the laser glass are heat-melted and composited, the appropriate crystal orientation is selected as needed for the composite. After the gain medium surface is bonded, a plurality of laser media to be composited are fixed with a high temperature resistant fixture, and placed in a vacuum high temperature furnace with a uniform temperature field for constant temperature heat-melting and composite. The heat-melting temperature varies according to the thermal properties and geometric dimensions of the material: the temperature is 0~100 ℃ higher than the softening point of the laser glass and 0~200 ℃ lower than the melting point of the laser crystal. The constant temperature heat-melting time is 5~15min. After heat-melting bonding, the temperature is rapidly cooled (greater than 10℃ / min) to the annealing temperature (50~100℃ lower than the transition temperature of the laser glass) and precisely annealed (keep at the annealing temperature for 20h, and cool to room temperature at a rate of less than 3℃ / h). A shorter heat-melting time can avoid the probability of crystallization of the laser glass and reduce the probability and degree of deformation of the glass or crystal.
[0018] Furthermore, in the hot-melt partition composite, the hot-melt temperature varies according to the thermal properties and geometric dimensions of the material, and the temperature is 0~100°C higher than the softening point of the laser glass and 0~200°C lower than the melting point of the laser crystal; the hot-melt partition composite time is 5~15 min.
[0019] Furthermore, in the hot-melt partition compounding, the hot-melt interface must satisfy a roughness Ra of less than 1 μm, and the hot-melt process is completed in a vacuum environment with a vacuum degree of -100 kPa.
[0020] Compared with the prior art, the present invention has the following advantages and technical effects: (1) The gain spectrum tunable laser medium based on structural compounding provided by the present invention has the characteristics of flexibly matching the gain medium matrix material; through the structural compounding of different matrix materials, the characteristics of multiple gain media can be obtained at the same time, and the gain spectrum can be regulated; in particular, according to the different emission characteristics of laser glass and crystal, the gain spectrum characteristics of the two are compounded, and the characteristics of high glass doping concentration, large bandwidth, high crystal thermal conductivity and optical anisotropy can be obtained at the same time; (2) The gain spectrum tunable laser medium based on structural compound provided by the present invention has the characteristic of flexible matching of activation ions; in order to realize wavelength tunable laser output in multiple bands, in the matrix material, partitioned doping can be realized through structural compounding of different activation ions, and gain can be obtained in multiple bands at the same time, so as to realize mutual complementation of gain spectra in different bands; in particular, partitioned doping based on different activation ions can effectively avoid unnecessary microscopic energy transfer between multiple activation ions, thereby improving the emission efficiency of the laser gain medium; (3) The gain spectrum tunable laser medium based on structural compound provided by the present invention can achieve the tailoring of the emission spectrum based on the cross-region energy transfer effect of the laser medium by flexibly matching the activation ions and the matrix materials, which is conducive to obtaining laser emission of special wavelengths; (4) The gain spectrum tunable laser medium based on structural compounding provided by the present invention has two structural compounding modes, namely series and parallel. By adjusting the relative structural ratio parameters of different gain media, the gain spectrum can be precisely controlled. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the structure of Er laser glass composite with multiple matrix structures is provided for Example 1 of the present invention; Figure 2 Provide an emission spectrum diagram of the structural composite Er laser glass for Example 1 of the present invention; Figure 3 Provide an emission spectrum and a structural schematic diagram of the Er-Tm structure composite laser glass for Example 2 of the present invention; Figure 4 Provides a preparation flow chart of Er-Tm-Ho structure composite laser glass for Example 3 of the present invention; Figure 5 Provide an emission spectrum diagram and an end face structure diagram of the Er-Tm-Ho structure composite laser glass for Example 3 of the present invention; Figure 6 Provide an emission spectrum diagram and a theoretical gain spectrum diagram of a Tm-Ho structure composite laser glass for Example 4 of the present invention; Figure 7 A schematic diagram of a Yb-doped glass-crystal structure composite laser medium is provided for Example 5 of the present invention; Figure 8 A schematic diagram of a Nd-doped glass-crystal structure composite laser medium is provided for Example 6 of the present invention; Fig. 9 A schematic diagram of an Er-doped glass-crystal structure composite laser medium is provided for Example 7 of the present invention. DETAILED DESCRIPTION
[0022] The following description combines specific illustrations to explain the technical solution so as to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and similar generalized embodiments made by ordinary technicians in this field without creative work are all within the scope of protection of the present invention.
[0023] Embodiment 1: In this embodiment, a method for preparing Er ion-doped laser glass composite with multiple matrix structures is provided, comprising the following steps: (1) Two types of Er laser glasses were prepared by the melting-annealing method. The composition of the first Er laser glass 1 was BaO-Ga2O3-GeO2-Er2O3, and the composition of the second Er laser glass 2 was BaO-ZnO-GeO2-Er2O3. The doping concentration of Er2O3 in the two laser glasses was 1 mol%.
[0024] (2) Cold processing of the hot melt interface of laser glass: Use 240 mesh, 600 mesh, 1000 mesh, 1500 mesh, and 2000 mesh sandpaper to roughly polish the hot melt interface, and then use 5 μm, 3 μm, 1 μm, and 0.05 μm polishing agents to finely polish the hot melt interface until the roughness Ra of the hot melt interface is less than 1 μm. The thickness of the first Er laser glass 1 is 2 mm, and the thickness of the second Er laser glass 2 is 3 mm.
[0025] (3) Hot-melt bonding of laser glass: The hot-melt interface of the first Er laser glass 1 and the second Er laser glass 2 is tightly fitted, and then the two laser glasses are fixed with a high-temperature resistant fixture and placed in a vacuum high-temperature furnace with a uniform temperature field. The temperature is raised to 790 °C at a heating rate of ≤7 °C / min, and hot-melted at a constant temperature for 5 minutes. After hot-melt bonding, the temperature is quickly cooled to the annealing temperature and precision annealed (annealing temperature 650 °C, kept at this temperature for 20 hours, and cooled to room temperature at a rate of 5 °C / h).
[0026] (4) Cold processing of structural composite laser medium: The annealed structural composite laser glass is taken out and polished to obtain a structural composite laser glass with two parallel surfaces and a size of 20×20×3 mm, wherein the thickness of the first Er laser glass 1 is 1 mm and the thickness of the second Er laser glass 2 is 2 mm. The schematic diagram of Er-doped laser glass composite with multiple matrix structures is shown in Figure 1 shown.
[0027] In this embodiment, the fluorescence spectra of the first Er laser glass 1, the second Er laser glass 2 and the structured composite laser glass under 980 nm laser diode pumping are tested by Zhuoli Hanguang fluorescence spectrometer. The 1.5 μm emission spectra of the three laser glasses are shown in Figure 2 As shown, from Figure 2 It can be seen that the central wavelength of the emission spectrum of the first Er laser glass 1 is closer to the short-wave region, which is 1547 nm; the central wavelength of the emission spectrum of the second Er laser glass 2 is closer to the long-wave region, which is 1563 nm; the emission spectrum of the structural composite laser glass is obviously flatter, which is conducive to achieving flat gain in the 1.5 μm band.
[0028] Embodiment 2: In this embodiment, a method for preparing an Er-Tm partition-doped structured composite bulk laser medium with an emission range covering 1450-2200 nm is provided, comprising the following steps: (1) Er laser glass and Tm laser glass were prepared by melt-annealing method. The composition of Er laser glass was BaO-Ga2O3-GeO2-Er2O3, where the doping concentration of Er2O3 was 1 mol%. The composition of Tm laser glass was BaO-Ga2O3-GeO2-Tm2O3, where the doping concentration of Tm2O3 was 1 mol%. The refractive index difference between the two laser glasses was less than 5 optical units.
[0029] (2) Cold processing of the hot melt interface of laser glass: Use wire cutting to cut a 10° bevel on the two laser glasses respectively; use 240 mesh, 600 mesh, 1000 mesh, 1500 mesh, and 2000 mesh sandpaper to rough polish the hot melt interface, and then use 5 μm, 3 μm, 1 μm, and 0.05 μm polishing agents to fine polish the hot melt interface until the roughness of the hot melt interface is less than 1 μm. The length of Er laser glass is 12 mm, and the length of Tm laser glass is 15 mm.
[0030] (3) Hot-melt bonding of laser glass: The hot-melt interface of Er laser glass and Tm laser glass is tightly fitted, and then the two laser glasses are fixed with a high-temperature resistant fixture and placed in a vacuum high-temperature furnace with a uniform temperature field. The temperature is raised to 790 °C at a heating rate of ≤7 °C / min, and hot-melted at a constant temperature for 9 minutes. After hot-melt bonding, the temperature is quickly cooled to the annealing temperature and precision annealed (annealing temperature 650 °C, kept at this temperature for 20 hours, and cooled to room temperature at a rate of 5 °C / h).
[0031] (4) Cold processing of structural composite laser medium: The annealed structural composite laser glass is taken out and polished on both sides to obtain a structural composite laser glass with two parallel sides and a size of 10×10×22 mm, where the length of the Er laser glass is 10 mm and the length of the Tm laser glass is 12 mm. The schematic diagram of the structural composite laser glass is shown in the figure. Figure 3 As shown in the inset, the composite interface with a 10° tilt can reduce the Fresnel reflection at the interface of the two laser glasses to some extent.
[0032] In this embodiment, the fluorescence spectrum of Er-Tm structure composite laser glass under 808nm laser diode pumping is tested by Zhuoli Hanguang fluorescence spectrometer. The infrared emission spectrum of Er-Tm structure composite laser glass is as follows: Figure 3 As shown, from Figure 3 It can be seen that the emission spectrum of the structural composite laser glass covers the 1450~2200 nm band, which is conducive to the realization of multi-wavelength tunable laser output in the 1.5~2.0 μm band.
[0033] Example 3 In this embodiment, a method for preparing a columnar laser medium with a structure composite of Er-Tm-Ho partition doping and an emission range covering 1450-2200 nm is provided. The preparation process is as follows: Figure 4 As shown, the following steps are included: (1) Er laser glass, Tm laser glass and Tm / Ho co-doped laser glass were prepared by melt-annealing method. The components of Er laser glass are BaO-Ga2O3-GeO2-Er2O3, where the doping concentration of Er2O3 is 1mol%. The components of Tm laser glass are BaO-Ga2O3-GeO2-Tm2O3, where the doping concentration of Tm2O3 is 1mol%. The components of Tm / Ho laser glass are BaO-Ga2O3-GeO2-Tm2O3-Ho2O3, where the doping concentrations of Tm2O3 and Ho2O3 are both 1mol%. Tm2O3 exists in the glass as a sensitizer of Ho2O3. The three laser glasses were cast in a special mold to obtain the shape of an isosceles triangular prism with an angle of 120°. The base of the isosceles triangular prism is 20 mm long and the height of the triangular prism is 100 mm.
[0034] (2) Cold processing of the hot-melt interface of laser glass: Use 240 mesh, 600 mesh, 1000 mesh, 1500 mesh, and 2000 mesh sandpaper to coarsely polish the two hot-melt interfaces of the isosceles triangular prism, and then use 5 μm, 3 μm, 1 μm, and 0.05 μm polishing agents to fine-polish the hot-melt interfaces until the roughness of the hot-melt interfaces is less than 1 μm.
[0035] (3) Hot-melt bonding of laser glass: The hot-melt interfaces of three laser glasses are tightly fitted, and then the three laser glasses are fixed with a high-temperature resistant fixture and placed in a vacuum high-temperature furnace with a uniform temperature field. The temperature is raised to 790 °C at a heating rate of ≤5 °C / min, and hot-melted at a constant temperature for 10 minutes. After hot-melt bonding, the temperature is quickly cooled to the annealing temperature and precision annealed (annealing temperature 650 °C, kept at this temperature for 20 hours, and cooled to room temperature at a rate of 5 °C / h).
[0036] (4) Cold processing of structural composite laser medium: The composite laser glass with equilateral triangular prism structure after annealing is taken out, the two ends are fixed and rounded and polished to obtain a columnar composite laser glass with a size of φ15×90 mm. The three types of laser glass are evenly divided into cylinders in space, and the angle occupied is 120°. The schematic diagram of the columnar composite laser glass is shown in the figure. Figure 4 shown.
[0037] In this embodiment, Er-Tm-Ho structured composite laser glass with two parallel surfaces and a thickness of 1 mm was cut and polished to the optical surface at both ends; the fluorescence spectrum of the structured composite laser glass under 808 nm laser diode pumping was tested using a Zhuoli Hanguang fluorescence spectrometer. The infrared emission spectrum of the structured composite laser glass is shown in Figure 5 As shown, from Figure 5 It can be seen that the emission spectrum of the structured composite laser glass covers the 1450-2200 nm band. Compared with the Er-Tm structured composite laser glass described in Example 2, this example supplements the gain of the Ho ion band of the laser medium, effectively improving the emission intensity of the laser medium at 1900-2200 nm. This is conducive to achieving ultra-wideband laser output in the 1.5-2.2 μm band.
[0038] Example 4 In this embodiment, a method for preparing a Tm-Ho partitioned doped composite sheet laser medium that is conducive to achieving Tm ion short-wave laser output is provided, comprising the following steps: (1) Tm laser glass and Ho laser glass were prepared by melt-annealing method. The composition of Tm laser glass was BaO-Ga2O3-GeO2-Tm2O3, where the doping concentration of Tm2O3 was 1 mol%. The composition of Ho laser glass was BaO-Ga2O3-GeO2-Ho2O3, where the doping concentration of Ho2O3 was 2 mol%.
[0039] (2) Cold processing of the hot melt interface of laser glass: Use 240 mesh, 600 mesh, 1000 mesh, 1500 mesh, and 2000 mesh sandpaper to coarsely polish the hot melt interface, and then use 5 μm, 3 μm, 1 μm, and 0.05 μm polishing agents to finely polish the hot melt interface until the roughness of the hot melt interface is less than 1 μm.
[0040] (3) Hot-melt bonding of laser glass: The hot-melt interface of Tm laser glass and Ho laser glass is tightly fitted, and then the two laser glasses are fixed with a high-temperature resistant fixture and placed in a vacuum high-temperature furnace with a uniform temperature field. The temperature is raised to 790 °C at a heating rate of ≤7 °C / min, and hot-melted at a constant temperature for 5 minutes. After hot-melt bonding, the temperature is quickly cooled to the annealing temperature and precision annealed (annealing temperature 650 °C, kept at this temperature for 20 hours, and cooled to room temperature at a rate of 5 °C / h).
[0041] (4) Cold processing of structural composite laser media: The structural composite laser glass after annealing is taken out and polished on both sides to obtain a structural composite laser glass with two parallel sides and different thicknesses.
[0042] According to the above method, three types of composite laser glasses with structures of Tm1Ho1, Tm1Ho2 and Tm1Ho3 were prepared, and their structural parameters are shown in Table 1: Table 1
[0043] In this embodiment, the fluorescence spectra of Tm laser glass and structured composite laser glass under 808 nm laser diode pumping were measured by Zhuoli Hanguang fluorescence spectrometer. The emission spectrum and theoretical gain spectrum of the structured composite laser glass are shown in Figure 6 As shown, from Figure 6 It can be seen that in the Tm-Ho partitioned doped structured composite laser glass, as the thickness of the Ho doped region gradually increases, the peak position of the theoretical gain spectrum of the structured composite laser glass blue-shifts from 1850 nm to 1800 nm. Compared with the Tm-doped laser glass, the Tm-Ho structured composite laser glass described in this embodiment is more conducive to achieving the short-wave laser output of Tm ions at 1700-1800 nm.
[0044] Example 5 In this embodiment, a method for preparing a sheet-shaped laser medium composited with Yb ion-doped laser glass and a crystal structure is provided, comprising the following steps: (1) Preparation of Yb laser glass and laser crystals: Yb-doped quartz glass is prepared by sol-gel method, 3D printing and other methods, and Yb-doped yttrium aluminum garnet (Yb: YAG) crystals are prepared by pulling method.
[0045] (2) Cold processing of the hot melt interface of laser glass and laser crystal: Select the appropriate Yb: YAG crystal orientation, and use 240 mesh, 600 mesh, 1000 mesh, 1500 mesh, and 2000 mesh sandpaper to roughly polish the hot melt interface of glass and crystal, and then use 5 μm, 3 μm, 1 μm, and 0.05 μm polishing agents to finely polish the hot melt interface until the roughness of the hot melt interface is less than 1 μm. The thickness of Yb laser glass and Yb: YAG crystal is 3 mm.
[0046] (3) Hot-melt bonding of laser glass and laser crystal: The hot-melt interface of Yb laser glass and Yb: YAG crystal is tightly fitted, and then the Yb laser glass and Yb: YAG crystal are fixed with a high-temperature resistant fixture and placed in a vacuum high-temperature furnace with a uniform temperature field. The temperature is raised to 1850°C at a heating rate of ≤10°C / min, and hot-melted at a constant temperature for 10 minutes. After hot-melt bonding, the temperature is quickly cooled to the annealing temperature and precision annealed (annealing temperature is 1750°C, kept at this temperature for 20 hours, and cooled to room temperature at a rate of 5°C / h).
[0047] (4) Cold processing of structured composite laser medium: The annealed structured composite laser medium is taken out and polished on both sides to obtain a structured composite laser medium with two parallel sides and a size of 20×20×4 mm, where the thickness of the Yb laser glass is 2 mm and the thickness of the Yb: YAG crystal is 2 mm. The schematic diagram of the Yb-doped laser glass-crystal structured composite laser medium is shown in Figure 1. Figure 7 shown.
[0048] Example 6 In this embodiment, a method for preparing a bulk laser medium composited with Nd ion-doped laser glass and a laser crystal structure is provided, comprising the following steps: (1) Preparation of Nd laser glass and laser crystals: Nd-doped quartz glass is prepared by sol-gel method, 3D printing and other methods, and Yb-doped gadolinium gallium garnet (Nd: GGG) crystal is prepared by pulling method.
[0049] (2) Cold processing of the hot melt interface of laser glass and laser crystal: Select the appropriate Nd: GGG crystal orientation, and use 240 mesh, 600 mesh, 1000 mesh, 1500 mesh, and 2000 mesh sandpaper to roughly polish the hot melt interface of glass and crystal, and then use 5 μm, 3 μm, 1 μm, and 0.05 μm polishing agents to finely polish the hot melt interface until the roughness of the hot melt interface is less than 1 μm. The thickness of Nd laser glass and Nd: GGG crystal is 3 mm.
[0050] (3) Melt bonding of laser glass and laser crystal: The hot melt interface of Nd laser glass and Nd: GGG crystal is tightly fitted, and then the Nd laser glass and Nd: GGG crystal are fixed with a high temperature resistant fixture and placed in a vacuum high temperature furnace with uniform temperature field. The temperature is raised to 1700 °C at a heating rate of ≤10 °C / min, and hot melted at a constant temperature for 10 minutes. After hot melt bonding, the temperature is quickly cooled to the annealing temperature and precision annealed (annealing temperature is 1600 °C, kept at this temperature for 20 hours, and cooled to room temperature at a rate of 5 °C / h).
[0051] (4) Cold processing of structured composite laser medium: The annealed structured composite laser medium is taken out and polished on both sides to obtain a structured composite laser medium with two parallel sides and a size of 20×20×4 mm, where the thickness of the Nd laser glass is 2 mm and the thickness of the Nd: GGG crystal is 2 mm. The schematic diagram of the Nd-doped structured composite laser medium is shown in Figure 2. Figure 8 shown.
[0052] Example 7 In this embodiment, a method for preparing a bulk laser medium composited with Er ion-doped laser glass and a laser crystal structure is provided, comprising the following steps: (1) Preparation of Nd laser glass and laser crystal: Er-doped laser glass with the composition of SiO2-Al2O3-La2O3-Er2O3 was prepared by melt-annealing method, where the doping concentration of Er2O3 was 1 mol%. Er-doped sodium lanthanum tungstate (Er: NLW) crystal was prepared by Czochralski method.
[0053] (2) Cold processing of the hot melt interface of laser glass and laser crystal: Select the appropriate Er: NLW crystal orientation, and use 240 mesh, 600 mesh, 1000 mesh, 1500 mesh, and 2000 mesh sandpaper to roughly polish the hot melt interface of glass and crystal, and then use 5 μm, 3 μm, 1 μm, and 0.05 μm polishing agents to finely polish the hot melt interface until the roughness of the hot melt interface is less than 1 μm. The thickness of Er laser glass and Er: NLW crystal is 3 mm.
[0054] (3) Hot-melt bonding of laser glass and laser crystal: The hot-melt interface of Er laser glass and Er: NLW crystal is tightly fitted, and then the Er laser glass and Er: NLW crystal are fixed with a high-temperature resistant fixture and placed in a vacuum high-temperature furnace with a uniform temperature field. The temperature is raised to 1150 °C at a heating rate of ≤5 °C / min, and hot-melted at a constant temperature for 15 minutes. After hot-melt bonding, the temperature is quickly cooled to the annealing temperature and precision annealed (annealing temperature is 1050 °C, kept at this temperature for 20 hours, and cooled to room temperature at a rate of 5 °C / h).
[0055] (4) Cold processing of structured composite laser medium: The annealed structured composite laser medium is taken out and polished on both sides to obtain a structured composite laser medium with two parallel sides and a size of 20×20×6 mm, where the thickness of the Er laser glass is 2 mm and the thickness of the Er: NLW crystal is 2 mm. The schematic diagram of the Er-doped structured composite laser medium is shown in Fig. 9 shown.
[0056] Compared with the existing laser gain media (such as laser glass and laser crystal), the gain spectrum adjustable laser medium based on structural composite of the present invention has the characteristics of flexible matching gain medium matrix material; through the structural composite of different matrix materials, the characteristics of multiple gain media can be obtained at the same time to achieve the regulation of gain spectrum. For example, for the series structure composite laser medium, the ratio of the series length of different types of laser media can be optimized to finally achieve the regulation of the gain spectrum of the structure composite laser medium; for the parallel structure composite laser medium, the ratio of the cross-sectional geometric dimensions of different types of laser media can be optimized to finally achieve the regulation of the gain spectrum of the structure composite laser medium; in the process of gain spectrum regulation, the regulation of the required characteristics of the gain spectrum is a nonlinear process, and the gain spectrum can be regulated by gradually changing the ratio of the series length or the ratio of the parallel cross-sectional geometric dimensions. Those skilled in the art can make specific applications and adjustments according to the characteristics of the waveguide structure model of the laser medium, the type of doped activation ions, the final regulation purpose, etc.
[0057] The above-described embodiments only express several implementation methods of the present invention, but should not be understood as limiting the scope of protection of the present invention. It should be pointed out that for those skilled in the art to which the present invention belongs, the supplement or optimization made to the present invention without departing from the concept of the present invention still falls within the scope of protection of the present invention.
Claims
1. A gain spectrum tunable laser medium based on structural compounding, characterized in that: It includes a plurality of different types of laser media with structural composites; the structural composite methods include series composite and parallel composite; the laser medium includes a matrix material and doped activation ions; the matrix material is laser glass, laser crystal or laser ceramic; the activation ions doped in the laser medium include rare earth ions, transition metal ions or heavy metal ions.
2. The gain spectrum tunable laser medium based on structural compounding according to claim 1, characterized in that: When the matrix materials of the plurality of different types of laser media are the same, the activated ions doped therein are different; When the active ions doped in the plurality of different types of laser media are the same, their matrix materials are different; Alternatively, the active ions doped in the multiple different types of laser media are different from the matrix materials.
3. The gain spectrum tunable laser medium based on structural compounding according to claim 1, characterized in that: In the multiple different types of laser media compounded in series, the multiple different types of laser media are pumped sequentially from one end to the other end in the order of the series connection, and the laser passes through the different types of laser media sequentially in the order when transmitting therein.
4. The gain spectrum tunable laser medium based on structural compounding according to claim 1, characterized in that: In the multiple different types of laser media compounded in parallel, the multiple different types of laser media are pumped simultaneously and generate multiple lights with different characteristics simultaneously, and the multiple lights are transmitted in the laser medium simultaneously.
5. The gain spectrum tunable laser medium based on structural compounding according to claim 1, characterized in that: Among the various types of laser media compounded in series, the hot-melt composite interface between adjacent laser media has a tilt angle of 0 to 10°.
6. The gain spectrum tunable laser medium based on structural compounding according to claim 1, characterized in that: The length of the laser medium is ≥3 μm in series recombination, and the cross-sectional diameter of the laser medium is ≥3 μm in parallel recombination.
7. The gain spectrum tunable laser medium based on structural compounding according to claim 1, characterized in that: In the composite interface of any two different laser media, the ion diffusion distance is ≤1.5μm.
8. A method for preparing a gain spectrum tunable laser medium based on structural compounding according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Prepare various types of laser media; S2, hot-melt partition compounding: the various types of laser media prepared in step S1 are closely bonded according to a set structural compounding method, thereby achieving hot-melt partition compounding to obtain a laser medium with adjustable gain spectrum after hot-melt compounding; S3. Cold processing of laser medium: cold processing is performed on the gain spectrum tunable laser medium after hot melt partition compounding according to the direction of the hot melt bonding interface, and finally a gain spectrum tunable laser medium with a structural compound is obtained.
9. The method according to claim 8, characterized in that In the hot-melt partition composite, the hot-melt temperature varies according to the thermal properties and geometric dimensions of the material. The hot-melt temperature is 0-100°C higher than the softening point of the laser glass and 0-200°C lower than the melting point of the laser crystal. The hot-melt partition composite time is 5-15 min.
10. The method according to claim 8, characterized in that In the hot-melt partition compounding, the hot-melt interface must satisfy the roughness Ra of less than 1 μm, and the hot-melt process is completed in a vacuum environment with a vacuum degree of -100 kPa.
Citation Information
Patent Citations
High-repetition-frequency tunable mode-locked fiber laser, laser generation method and application
CN109361144A
Bonding method of laser disc crystal
CN113054517A
Trapezoidal bonding passive Q-switched laser module
CN113206432A
Solid-state laser oscillator
JP2002057388A
Multiform crystal and apparatus for fabrication
US5394420A
